The Implementation of the Assemblr Edu AR: Biodigest Application on Student Learning Outcomes in Digestive System Material at SMA Batik 2 Surakarta - Nur Fatikhah Mawarni; Ima Aryani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to examine the effect of implementing the Assemblr Edu AR: BioDigest application on students’ cognitive learning outcomes and to evaluate student engagement in the affective and psychomotor domains during instruction on the digestive system in Grade XI at SMA Batik 2 Surakarta. This study employed a quasi-experimental method using a nonequivalent control group design. The research sample consisted of two classes: XI EIPA 1 as the control class, which used PowerPoint media, and XI EIPA 2 as the experimental class, which used the Assemblr Edu AR: BioDigest application. Data were collected through learning achievement tests and validated observation sheets, and were analyzed using an independent samples t-test and N-gain analysis. The results showed a significant difference between the experimental and control classes in cognitive learning outcomes (p < 0.05). The effectiveness of the instructional media in the experimental class was indicated by an N-gain score of 0.5944, which falls within the moderate category. In the affective and psychomotor domains, the experimental class also demonstrated higher levels of engagement than the control class. These findings indicate that three-dimensional visualization and interactive features in augmented reality can enhance conceptual understanding, learning motivation, and student skills by providing a more meaningful learning experience. Theoretically, this study contributes to strengthening research on augmented reality-based learning. Practically, it offers an innovative alternative instructional medium for biology education, particularly for abstract and complex topics.